Government debt and economic growth in Malaysia: the role of institutional quality - Daud S.N.M.; Podivinsky J. (Routledge, 2024)
We examine the role of economic freedom in the debt-growth model. There is evidence of the contingency effect of institutional quality on the relationship between government debt and economic growth. 2014, Taylor & Francis.